Accessing a Medicinal-Chemistry-Relevant Chemical Space with sp2–sp3 Hybrid Heterocyclic Fragments - Mato, Raquel; Bournez, Colin; Lefebvre, Quentin (Synthesis, 2024)
Target-first drug discovery relies heavily on protein structure information, which severely limits its application. In recent years, fragment-based drug Design (FBDD) has been identified as an alternative solution, where screening of smaller molecules for lower affinity allowed the use of focused libraries with a higher hit rate. It is shown that coupling an sp2-rich heteroaromatic group with a monofunctional sp3-rich core gives fragments (186 examples) with advantageous physical-chemical properties, covering a chemical space often neglected in traditional libraries.
Keywords: fragment-based drug design; azetidine; oxetane; medicinal chemistry; aqueous solubility; logP